Implikasi Dissenting Opinion Hakim Mahkamah Konstitusi dalam Perkara Perselisihan Hasil Pemilihan Umum (PHPU) Presiden dan Wakil Presiden Tahun 2024 - M. Giovani Fernanda; Lego Karjoko; Hari Purwadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The 2024 Presidential and Vice Presidential PHPU case contained a dissenting opinion, which had never happened before. This research aims to analyze the dissenting opinions of Constitutional Court Judges in the PHPU dispute for the President and Vice President and the implications of the dissenting opinion for the upcoming election. The research method is normative juridical. The type of data used is secondary data. The data analysis technique uses a data interpretation method with deductive reasoning which is presented descriptively. The results of this research are: first, the Dissenting opinion of the Constitutional Court Judge in the 2024 Presidential and Vice Presidential PHPU case, namely: Constitutional Justice Saldi Isra assessed that the distribution of social assistance during elections has the potential to cause a conflict of interest, so that the Petitioner's petition relating to social assistance is legally grounded; Constitutional Justice Arief Hidayat, based on systematic and grammatical interpretation, is of the opinion that the President/Vice President's right to campaign is used when the President/Vice President pair becomes the President/Vice President candidate pair in an election contest; Constitutional Justice Enny Nurbaningsih believes that there has been non-neutrality of officials in several regions, so the Court should order re-voting for several of these regions. Second, the implications of dissenting opinions on the upcoming election can be used as a basis for the implementation of future elections, so that there are improvements both in terms of regulations, institutions and implementation that must be carried out by legislators and election organizers in order to increase the integrity and credibility of elections.